O cinema limítrofe de David Lynch - Ferraraz, Rogério (2003)
This dissertation is a survey of the films by the American director David Lynch in order to elucidate bis ethical and aesthetic concerns. His films both explore narrative conventions and renew cinematographic language. They establish what I define as a "borderline cinema". He develops a kind of hiper-realism or super-realism, by creatively mixing styles, forms and themes from several film genres and styles. The study departs from close readings of Lynch's feature films Eraserhead (1977), The Elephant Man (1980), Blue Velvet (1986), Wild at Heart (1990), Twin Peaks - Fire Walk With Me (1992), Lost Highway (1997), The Straight Story (1999) and Mulholland Drive (2001), as well as the TV series Twin Peaks (1990-1991). However, the analysis occasionally includes a consideration of bis short films, the feature film Dune (1984), bis other television productions, bis paintings, photography, furniture design and more recent work on the internet. Lynch's movies show some recurrent characteristics and themes, qualifying him as an auteur. Some of these characteristics include appropriations and new readings of movies by other directors, such as Hitchcock, Bunuel and Kubrick, or film genres, such as science-fiction, film noir, horror movies, thrillers and road movies. Far from simply adhering to generic conventions, Lynch uses the main clichés of those genres to subvert them. There are echoes of films from various periods and schools, as well as of fine arts and literature. This aesthetic amalgam produces a "borderline cinema", that is based on contrasts and analogies of illusion and reality, sanity and madness, inner and outside worlds, adult and child universes. In this way, Lynch arouses a feeling of the uncanny in the spectator, according to the Freudian concept. He mixes, as in a puzzle, ideas of transparency and opacity, producing narratives that are both illusionistic and anti-illusionistic